Pengembangan Media Kartu Kebangsaan Berbasis Augmented Reality 3D untuk Penguatan Karakter Kewarganegaraan dan Kesadaran Global Siswa SMP Sunan Averroes Yogyakarta - Rassyi, Sultan Fakhrur; Isro’ullaili (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to: (1) develop a 3D augmented reality-based National Identity Card learning media; (2) assess the feasibility of the media; (3) evaluate the practicality of the media; and (4) test the effectiveness of the media in strengthening civic character and global awareness among students of SMP Sunan Averroes Yogyakarta. This research is a type of Research and Development (R&D) conducted at SMP Sunan Averroes Yogyakarta. The product validation involved two expert lecturers. The test subjects consisted of a civic education teacher and eighth-grade students. Data collection techniques included observation, interviews, and questionnaires. Feasibility and practicality data were obtained from expert validation (content and media), teacher assessments, and student responses. The effectiveness of the learning media was analyzed using a t-test with a significance level of 0.05. The results showed that: (1) the National Identity Card learning media was successfully developed through a systematic process using the ADDIE model in five stages. The first stage, analysis, involved needs analysis, curriculum analysis, and student characteristic analysis. The second stage, design, focused on conceptualizing the media and designing AR features. The third stage, development, included application modeling and instrument validation. (2) The feasibility test results showed a score of 75.7% from the content expert (categorized as feasible) and 82.2% from the media expert (categorized as very feasible). (3) The practicality test results showed a score of 99.1% from the teacher and 86.4% from students (categorized as very feasible). The fourth stage, implementation, involved applying the media in the classroom, and the fifth stage, evaluation, included feedback analysis from the teacher and student responses to assess effectiveness and improve the media. (4) The National Identity Card learning media proved to be effective, as evidenced by the experimental class surpassing the minimum mastery criterion of 75, with an average score of 89.10 and a 16.78% increase in civic character, and an average score of 86.10 with an 18.36% increase in global awareness, both higher than those of the control class.